Wrist-worn wearables for atrial fibrillation detection: diagnostic performance of PPG versus single-lead ECG – a review - Dobrosielska, Adrianna; Woźniakowska , Iga; Zambrzycka, Maja; Misarko, Aleksandra; Jedwabnik, Monika; Ścigała, Stanisław; Peszuk, Krzysztof; Lech, Weronika; Krajewski, Hoang Viet; Olszewski, Bartosz (Quality in Sport, 2026)
Background: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and an important cause of stroke and reduced quality of life. Standard methods such as 12-lead electrocardiography and Holter monitoring cover only limited periods and are not ideal for repeated screening. Wrist-worn devices, including smartwatches and fitness bands, are now part of a healthy lifestyle and are widely used by athletes and physically active individuals. Many record photoplethysmography (PPG), single-lead electrocardiography (ECG), or both, but their diagnostic value in AF detection is still not fully established. Aim: To compare the diagnostic performance of wrist-worn devices using PPG and single-lead ECG for AF detection in adults. Material and methods: A systematic PubMed search was performed using smartwatch- and AF-related terms. The search was limited to the last five years, English language, human studies, and free full-text articles. Of 44 records, 13 original studies were included after screening. Results: In controlled cohorts with good signal quality, PPG-based algorithms usually showed sensitivity and specificity around 94–95% or higher. In real-world settings, especially in older post-stroke patients, sensitivity of irregular rhythm notifications was much lower, around one third, although specificity reached 100%. Single-lead ECG smartwatches and ambulatory ECG recorders usually achieved sensitivity and specificity above 90%. Physician interpretation of smartwatch ECG recordings improved diagnostic accuracy. Conclusions: Both PPG- and ECG-based wrist-worn devices can detect AF with high accuracy in selected settings. In routine practice, ECG-based devices seem more reliable, while PPG results are more dependent on signal quality and algorithm design. Positive findings should still be confirmed by standard ECG.